Circulating Chromogranin B Is Associated With Left Ventricular Functional Recovery After Successful Recanalization of Chronic Total Occlusion - Shen, Ying; Aihemaiti, Muladili; Shu, Xin Yi; Yang, Chen Die; Chen, Jia Wei; Dai, Yang; Ding, Feng Hua; Yang, Zhen Kun; Hu, Jian; Zhang, Rui Yan; Lu, Lin; Wang, Xiao Qun; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Chromogranin B (CgB) is increased in heart failure and proportionate to disease severity. We investigated whether circulating CgB level is associated with left ventricular (LV) functional recovery potential after successful recanalization of chronic total occlusion (CTO). Methods: Serum levels of CgB were assayed in 53 stable angina patients with LV functional recovery (an absolute increase in LV ejection fraction [EF] by ≥ 5%) and 53 age- and sex-matched non-recovery controls after successful recanalization of CTO during 12-month follow-up. Results: We found CgB level was significantly lower in the recovery than in the non-recovery group (593 [IQR 454~934] vs. 1108 [IQR 696~2020] pg/mL, P<0.001), and was inversely correlated with changes in LVEF (Spearman’s r=-0.31, P=0.001). Receiver operating characteristic (ROC) analysis showed that area under the curve of CgB for predicting LVEF improvement was 0.760 (95% CI 0.664~0.856) and the optimal cut-off value was 972.5 pg/mL. In multivariate analyses, after adjusting for confounding factors, high CgB level remained an independent determinant of impaired LV functional recovery after CTO recanalization. LV functional improvement appeared to be more responsive to CgB in patients with poor than with good coronary collaterals. Conclusions: Elevated circulating CgB level confers an increased risk of impaired LV functional recovery after successful recanalization of CTO in patients with stable coronary artery disease.